Pengaruh Digitalisasi Pembayaran Pajak Terhadap Kepatuhan Pajak Usaha Mikro, Kecil, dan Menengah (Studi Kasus pada UMKM di Surakarta) - Amalina Fatika Putri; Fadjar Harimurti; Aris Eddy Sarwono (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research investigates the impact of digital tax payment methods on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) located in Surakarta City. It hypothesizes that a digitalized tax system will enhance efficiency and convenience for taxpayers, thereby fostering greater compliance. Employing a quantitative methodology, the study utilizes a simple linear regression approach for its analysis. The participant pool comprises all active MSME operators in Surakarta City who possess a Taxpayer Identification Number (NPWP). A total of 90 respondents were carefully selected to form the sample. Data collection was performed via questionnaires designed to assess both tax payment digitalization indicators and MSME tax compliance levels. Initial findings reveal that the majority of participants are productive-aged women, engaged primarily in the culinary, retail, fashion, and creative services industries, with most businesses having operated for over three years. These preliminary observations establish a foundational understanding of the characteristics of Surakarta's MSMEs as the subject of this study. Subsequent analysis will focus on rigorously testing the hypothesized causal link between digitalization and tax compliance.